A STUDY OF THE MAXWELL-CHERN-SIMONS-LIKE MODEL AS A QUANTUM FIELD THEORY - Priambodo (NIM 202 05 012) , Ronggo
Abstract : The Maxwell-Chern-Simons-like model is a model that is constructed to modify Maxwell theory through a Chern-Simons-like term. The aim is to describe electrodynamics which is gauge invariant, but its Lorentz and CPT symmetries are broken. Such a Chern-Simons-like term is characterized by an external constant vector and may emerge from a more fundamental theory, either spontaneously or dynamically. Because nature at present does not exhibit those two violations, there are some strict limits for the modification to be possible. Therefore, in order of this model to be accepted, besides compatible to observational and experimental results, the fundamental properties of quantum field theories should also be satisfied. In this thesis, the aspects of the Maxwell-Chern-Simons-like model is studied, especially gauge symmetry and field quantization.